RADIOFREQUENCY THERMAL ABLATION IN THE MANAGEMENT OF PAINFUL BONE METASTASES: INTERVENTIONAL STRATEGIES AND ONCOLOGICAL OUTCOMES - de Lima, Victor Hugo Moreira; Oliveira, Paulo Renê Faria de Almeida; de Freitas, Flávio Vinicius Rodrigues; da Silva, Ronaldo Pereira; da Silva, Jennifer Nascimento; Oliveira, Kelly Cristina Alberto; Ullrich, Caroline Santana; Salgado, Maria Thereza Santos Bandeira; da Costa, Anna Catharinna; dos Passos, Muriel Pereira (Seven Editora, 2026)
Bone metastases are a frequent complication of advanced cancer, associated with intense pain, structural instability, and significant functional impairment. Radiofrequency ablation (RFA) emerges as an effective minimally invasive strategy in the management of these lesions, promoting tumor necrosis through controlled thermal energy. This study aimed to analyze interventional strategies associated with RFA in the treatment of painful bone metastases, as well as to discuss their clinical and oncological results in light of recent evidence. This is an integrative literature review, with searches in international databases, using descriptors related to bone metastases, radiofrequency, thermal ablation, vertebroplasty, and pain control. Clinical studies, systematic reviews, and meta-analyses published between 2021 and 2026 were included. The results demonstrate that RFA provides rapid and sustained pain relief, functional improvement, and a reduction in opioid use. When combined with vertebroplasty, cementoplasty, or internal fixation, it also contributes to mechanical stabilization and prevention of pathological fractures. Evidence also indicates potential for local tumor control in selected cases. The technique presents a favorable safety profile, with a low complication rate when performed under adequate image guidance. It is concluded that radiofrequency ablation constitutes a safe, effective, and integrated approach to multidisciplinary oncological care, expanding therapeutic possibilities in the control of painful bone metastases.